GOVERNANCE IN CAPITAL MARKET INSTITUTIONS - Aras, Guler; Yobas, Banu (EMERALD GROUP PUBLISHING LTD, 2013)
The governance of capital market institutions did not receive much interest compared to their banking sector counterparts, partly due to their different ownership structures. Recent trends; increased competition, technological advances, structural changes, globalization, all had their share of impact on governance systems of capital markets institutions particularly on exchanges. Corporate governance of non-financial firms and capital markets institutions differ in several ways. Firstly the role of risk management differs since they may impose systemic risks to the financial system. Secondly well-implemented governance structures and processes are required but are not sufficient in capital markets since there are several conflicts of interests to be addressed. Therefore whether and how effectively they function is what matters. Thirdly the governance structures of such institutions exhibit different effectiveness on their decisions. The governance of FIs in capital markets is discussed in terms of board structure and management, risk governance, supervisors, shareholders, executive compensation, role of regulators, authorities and values and culture. The role of stock exchanges in corporate governance are discussed separately in terms of implementing corporate governance codes, demutualisation and its impact on regulations, transparency and accountability issues and the effects of M&As among exchanges. Market needs strong analytical tools and reliable benchmarks to assess governance risk. The corporate control and the regulation of the institutions by the exchanges when the corporations (regulated) are the competitors of the exchanges (regulators) or owned by the stockholders of the exchanges must be addressed. The risk of regulatory arbitrage, calls for the need of harmonisation among regulators. Better regulation of FIs and greater global coordination among regulators are seen as the most two important issues to prevent another crisis.
Keywords: Corporate governance; capital markets; stock exchanges; market power; Business & Economics